2021
DOI: 10.15581/003.34.2.87-105
|View full text |Cite
|
Sign up to set email alerts
|

Food brands, YouTube and Children: Media practices in the context of the PAOS self-regulation code

Abstract: The objective of this study is to analyze media practices involving food content on YouTube in terms of the self-regulatory framework established by the PAOS code, which was originally designed for television. The study considers content created and disseminated by two different sources: food brands and child YouTuber channels. We conducted an exploratory qualitative-quantitative study based on a content analysis of videos posted in 2019 on the most viewed YouTube channels in Spain (Socialblade, 2019). The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Thus, following Tatlow-Golden & Garde, 2020 [ 4 ] y Sacks & Looi, 2020 [ 17 ] it can be observed how the predominant path is that of the self-regulation. However, the analysis indicates how, with the exception of the US and Ireland, no express mention is made on platforms such as social networks in which food brands exert increasing pressure [ 15 , 48 ]. Therefore, they are firmly entrenched among the media diet of children and adolescents [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, following Tatlow-Golden & Garde, 2020 [ 4 ] y Sacks & Looi, 2020 [ 17 ] it can be observed how the predominant path is that of the self-regulation. However, the analysis indicates how, with the exception of the US and Ireland, no express mention is made on platforms such as social networks in which food brands exert increasing pressure [ 15 , 48 ]. Therefore, they are firmly entrenched among the media diet of children and adolescents [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along with these measures, of which it is necessary to observe their degree of effectiveness and scope, it is considered that public policies that promote healthy diets among children and adolescents should be taken. On the one hand, because a healthy eating is considered a human right [ 15 ]. On the other hand, from the scientific community it is observed that the intake of HFSS food can be a potential catalyst of obesity and it must be taken into account that this type of non-communicable diseases imply a medical cost.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations